Rekomendasi Pemilihan Smartphone Menggunakan Metode TOPSIS - Deva Eliza; Defri Ahmad (UNIVERSITAS NEGERI PADANG, 2022)
Smartphone is one of electronic devices in the form of communication tool which in this time the development following market demand. There are many kind of smartphone in the market with various criteria such as price, storage, ram, front camera, main camera and processor. This matter cause many consumers confuse to choose smartphone they will buy, it because there are various type, specification, and price offered when someone make decisions to purchase smartphone. Many consumers always mistakenly choose smartphone according to their need can't be denied. So that smartphone recommendation election be required. The purpose of this research are to know which criteria would be priority of the best smartphone election and to know recommendation in smartphone election based on alternative and criteria selected. The method which can be used to solve smarphone selection problem is Technic for Order Preference by Similarity to Ideal Solution (TOPSIS). The best smartphone recommendation based on budget range is Oppo A52, midranger is Vivo V20 2021, flagship is Asus Zenfone 6 ZS630KL, premium is Xiaomi Mix Alpha.